Integrating Entrepreneurship and Digital Skills in Salafiyah Islamic Boarding School Curriculum Planning - Anugrah, Widea; Nugraha, Mulyawan Safwandi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2026)
This study aims to analyze the educational planning at Pesantren Al-Mardiyyatul Islamiyyah, a Salafiyah pesantren that has adopted innovations in its curriculum by integrating religious education with practical skills such as entrepreneurship and information technology. The research was conducted through interviews with the head of the pesantren, curriculum managers, and teachers, as well as field observations and document analysis. The findings revealed that although the pesantren has made efforts to integrate digital skills into the curriculum, limited resources, such as technological facilities and teacher training, are the main barriers to full implementation. Stakeholder involvement in educational planning at Pesantren Al-Mardiyyatul Islamiyyah was found to be adequate, although some other pesantren do not engage all relevant parties. Data-driven evaluation, however, was not fully implemented, hindering the accurate measurement of educational planning success. The study recommends the development of a more relevant curriculum, enhanced technological facilities, and the implementation of data-driven evaluation systems to improve the quality of education. Prospects for further research include the implementation and testing of the proposed solutions to optimize the use of technology in pesantren education.